Transformational Leadership Model of School Principals in Ensuring the Sustainability of the GEREM ASEM Program Based on Community Partnerships - Rena Komalasari; Ujang Jamaludin; Yuyu Yuhana (MASI Mandiri Edukasi, 2026)
Many elementary school innovation programs fail to sustain due to weak resource mobilization and limited social collaboration between schools and communities. This study aims to formulate a transformational leadership model for school principals to ensure the sustainability of the GEREM ASEM (Education Movement with Real Action Together with the Community) Program based on community partnerships at SD Negeri Kaloran Kidul, Serang City. This study employed a qualitative case study design. Research informants were selected purposively, consisting of the principal, teachers, education staff, school committee members, parents, and community representatives directly involved in the program. Data were collected through participant observation, semi-structured in-depth interviews, and document analysis. Data analysis used the Miles and Huberman interactive model encompassing data reduction, data presentation, and conclusion verification, supported by source and technique triangulation to ensure credibility. The results reveal that the principal's transformational leadership model is structured through five strategic stages: (1) situational analysis and vision alignment, (2) formation of a program structure based on action pillars, (3) mobilization of human resources and partnerships, (4) participatory communication and branding strategies, and (5) continuous reflective evaluation. These stages successfully integrate the four dimensions of transformational leadership — idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration — resulting in strengthened student character (responsibility, honesty, and independence) and significantly increased active community participation in educational activities. This model is replicable as a reference for managing social partnership-based educational innovations in elementary schools.